Respostas

2014-02-03T11:57:39-02:00
Olá Paty!

Dada a equação matricial:

  \left[\begin{array}{ccc}-1&4&5\\0&2&7\\1&-1&-2\end{array}\right] +  \left[\begin{array}{ccc}3&5&2\\-1&5&3\\4&2&2\end{array}\right] =X+  \left[\begin{array}{ccc}2&7&2\\8&-1&-3\\-1&9&5\end{array}\right]

Podemos reescreve-lá por:

  \left[\begin{array}{ccc}2&9&7\\-1&7&10\\5&1&0\end{array}\right] =\left[\begin{array}{ccc}x_{11}+2&x_{12}+7&x_{13}+2\\x_{21}+8&x_{22}-1&x_{23}-3\\x_{31}-1&x_{32}+9&x_{33}+5\end{array}\right]

Feito isso, temos uma série de equações:

x_{11}+2=2\to x_{11}=0\\
\\
x_{12}+7=9\to x_{12}=2\\
\\
x_{13}+2=7\to x_{13}=5\\
\\
...

Assim, obtemos que a matrizX é:

X=  \left[\begin{array}{ccc}0&2&5\\-9&8&13\\6&-8&-5\end{array}\right]

Abraço,

Douglas Joziel. 
31 4 31